2019
DOI: 10.1124/mol.119.118315
|View full text |Cite
|
Sign up to set email alerts
|

hsa-miR-9-3p and hsa-miR-9-5p as Post-Transcriptional Modulators of DNA Topoisomerase IIαin Human Leukemia K562 Cells with Acquired Resistance to Etoposide

Abstract: microRNAs (miRNAs) are short, noncoding RNAs that inhibit translation by binding primarily to the 3′‐untranslated region (3′‐UTR) of mRNA. The enzyme TOP2α induces covalent complexes with DNA and produces transient double‐strand DNA breaks crucial for processes such as replication and normal chromosomal dysjunction at mitosis. TOP2α is an important target for clinically effective anticancer agents, such as etoposide (VP‐16) since these drugs stabilize the otherwise short‐lived enzyme‐DNA covalent complexes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 84 publications
(117 reference statements)
2
14
0
Order By: Relevance
“…The location of the human TOP2A gene is on chromosome 17, and its expression is associated with cell proliferation and the cell cycle; its production and degradation are regulated by the cell cycle, and it decreases rapidly after completing mitosis ( 11 , 12 ). Previous studies have reported that the accumulation of the TOP2A protein occurs due to the stable upregulation of TOP2A transcription ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The location of the human TOP2A gene is on chromosome 17, and its expression is associated with cell proliferation and the cell cycle; its production and degradation are regulated by the cell cycle, and it decreases rapidly after completing mitosis ( 11 , 12 ). Previous studies have reported that the accumulation of the TOP2A protein occurs due to the stable upregulation of TOP2A transcription ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…a number of studies have considered mir-9-5p and mir-9-3p as a single combined entity (29,30). mir-9/9 * .…”
Section: Discussionmentioning
confidence: 99%
“…Ma X et al found that miR-374a, miR-92a, and miR-106a increase drug resistance and promote growth and metastasis of lung cancer [9]. Kania EE et al also reported that miR-9-3p and miR-9-5p decrease DNA topoisomerase IIα expression levels in acquired resistance to etoposide and may act as biomarkers of responsiveness to TOP2-targeted therapy [10]. However, the mechanisms of miRNAs in the adenoma transformation to adenocarcinoma remain unknown.…”
Section: Introductionmentioning
confidence: 99%